TRANSFORMASI PENDIDIKAN PESANTREN PADA ABAD 21 - Much Hasan Darojat (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2021)
This article discusses the role of Islamic boarding schools in preparing the nation's generation in the early 21st century. The century marked by the swift currents of globalization and technological advances affects the emergence of changes (disruptions) in several aspects of life, including the world of Islamic education, especially Islamic boarding schools. For this reason, this thinking institution is able to answer the challenges of this century with global competencies such as: creative (creative thinking), critical thinking (critical thinking), collaboration (collaboration), and communication (communication). Islamic boarding schools that have long historical roots in the archipelago have a big role in developing the development of alumni. The various needs needed to face the 21st Century have been applied in the pesantren environment, they only need to be strengthened in their programs. In pesantren, the students are taught technical (hard-skills) and non-technical (soft-skills) which trains them to prepare for life in the community. With these two skills, pesantren alumni are proven to be able to face their times. Management of learning pesantren to continue to be creative and able to face the challenges of this century from several aspects of the curriculum that is carried out, institutional activities, and roles in society. This article also tries to explain some important issues in the pesantren world and how pesantren managers do not lose their footing and principles on their identity